Field Displacement-Based Inverse Method for Elastic and Viscoelastic Constitutive Properties - Nsengiyumva, G.; Kim, Y-R. (Experimental mechanics, 2022)
Background Mechanical characterization of materials that solely relies on global responses may overlook important local behavior that significantly affects the characterization of material properties. Field displacements such as from digital image correlation (DIC) can provide high-fidelity experimental data, which combined with finite element method (FEM) can form DIC-FEM inverse method that can better account for complex mechanical properties of materials. Despite its capability, the DIC-FEM inverse method has been mainly applied to an elastic-dominant regime even though inelastic deformation is important in many engineering materials. Specifically, the DIC-FEM inverse method has not been fully extended to viscoelastic materials due to the complex representation of the time-dependent modulus. Objective This study aimed at establishing a DIC-FEM inverse framework to identify constitutive properties of homogeneous elastic and viscoelastic materials. Methods Two example materials (i.e., polyetheretherketone (PEEK) and a viscoelastic fine aggregate matrix (FAM) with a bituminous binder) were selected for the elastic and viscoelastic investigation, respectively. Both were experimentally tested using three-point bending incorporated with DIC. FEM simulated the experiment and the Nelder-Mead nonlinear optimization algorithm was implemented to solve the inverse problem. Results The DIC-FEM inverse method successfully identified Young’s modulus of an example linear elastic PEEK and the linear viscoelastic relaxation modulus of FAM. Conclusions The resulting DIC-FEM inverse method is applicable to various materials with inelastic deformation and can be extended to localized behavior induced by microstructure heterogeneity and fracture.